2013
DOI: 10.2478/s11687-013-0140-4
|View full text |Cite
|
Sign up to set email alerts
|

Parasite fauna of Golden Grey Mullet Liza aurata (Risso, 1810) collected from Lower Kızılırmak Delta in Samsun, Turkey

Abstract: 269 SummaryThe mugilids are among the most cosmopolitan teleost fishes and they are widely distributed in fresh, brackish and coastal marine waters of the tropical and temperate regions of the world. Liza aurata is one of eight mugilid species survive in Turkish waters. Parasite fauna of the golden grey mullet Liza aurata (Risso, 1810) collected from Lower Kızılırmak Delta in Samsun, Turkey were investigated in the present study. Standard parasitological investigation methods were applied and standard indices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Öztürk and Çam (2013) This study Öztürk and Çam (2013) Protozoan infestations on fish, including trichodinids, are strongly dependent on ecological conditions such as temperature, high organic loads, and deterioration of water quality (Özer and Yılmaz Kırca, 2013). In the present study, the Lower Kızılırmak Delta showed seasonal differences in water temperatures, while dissolved oxygen, salinity, and nitrate were more constant throughout the seasons (see Table 4).…”
Section: Pomatoschistus Marmoratus Risso 1810mentioning
confidence: 53%
See 2 more Smart Citations
“…Öztürk and Çam (2013) This study Öztürk and Çam (2013) Protozoan infestations on fish, including trichodinids, are strongly dependent on ecological conditions such as temperature, high organic loads, and deterioration of water quality (Özer and Yılmaz Kırca, 2013). In the present study, the Lower Kızılırmak Delta showed seasonal differences in water temperatures, while dissolved oxygen, salinity, and nitrate were more constant throughout the seasons (see Table 4).…”
Section: Pomatoschistus Marmoratus Risso 1810mentioning
confidence: 53%
“…Most of the fish species examined here were found to be infested by several trichodinid species at different infestation values. Trichodinid infestations on gobiid fishes and L. aurata in the same sampling data have been the subject of other publications (Özer and Yılmaz Kırca, 2013;Öztürk and Çam, 2013); thus, they were excluded from discussion here. As can be seen in Table 1, it is obvious that most of the studies on trichodinids have been conducted in the same geographical region (4) where this study was carried out (see Figure 1 for details), and all comparable data on the fish-trichodinid relationships, including data from this study, have been produced by the authors of this study (see Table 1 for details).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent infection of fish by different pathogens/parasites is common in nature (Kotob, Menanteau‐Ledouble, Kumar, Abdelzaher, & El‐Matbouli, ); however, records on this topic are limited. Coexistence of myxozoans and helminths in fish was reported in Kristmundsson and Richter () and Özer and Kirca ().…”
Section: Introductionmentioning
confidence: 58%
“…ovonucleata Raabe, 1958 infecting a large number of marine host species and species such as T. tenuidens Faure-Fremiet, 1944 in fresh water and T. jadranica Raabe, 1958 parasitizing only a couple of marine host species (Özer 2003a, ÖztÜrk & Özer 2008, Padua et al 2012, Valladão et al 2013. Moreover, Trichodina puytoraci Lom, 1962 and T. lepsii Lom, 1962 have been reported from only mugilids, such as the striped mullet, Mugil cephalus Linneaus, 1758, and the golden grey mullet, Liza aurata Risso, 1810 in brackish water (Bykovskaya-Pavlovskaya et al 1964, Kinne 1984, Grupcheva et al 1989, Özer & ÖztÜrk 2004, Özer & Yilmaz Kirca 2013. Xu (2007) made detailed revision on the identification of T. gobii Raabe, 1959, previously reported either T. domerguei gobii or T. jadranica by some authors (Raabe 1959, Lom 1970, Grupcheva et al 1989, Su & White 1995, Madsen et al 2000, summarized its host range and suggested that T. gobii is a widely distributed species that belonged to one of the extraordinary fish trichodinids occurred in both marine and freshwater environments.…”
Section: Introductionmentioning
confidence: 99%